2023
DOI: 10.1055/s-0043-1767781
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Neurological Symptoms in Long COVID and Clinical Management

Abstract: Long COVID is a clinical diagnosis generally referring to the persistence or development of new symptoms, affecting multiple organ systems after SARS-CoV-2 COVID-19 infection. Long COVID is thought to affect ∼20% of people after infection, including all age ranges and severity of infection. Fatigue, postexertional malaise, and respiratory and cardiac symptoms are commonly described. Neurological symptoms such as cognitive changes, sensory disturbances, headaches, and dysautonomia are common as well. The underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Hypotheses on pathogenic mechanisms implicate both systemic effects and sequelae from acute SARS-CoV-2 organ injury. Hyperinflammation ( Proal and VanElzakker, 2021 ), abnormal immunological response and autoimmunity ( Leng et al, 2023 ), viral persistence ( Sherif et al, 2023 ), reactivation of latent Epstein-Barr virus ( Su et al, 2022 ), microvascular dysfunction ( Navis, 2023 ) , as well as coagulopathies and endotheliopathy ( Leng et al, 2023 ) have been suggested in the etiopathogenesis of PCS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypotheses on pathogenic mechanisms implicate both systemic effects and sequelae from acute SARS-CoV-2 organ injury. Hyperinflammation ( Proal and VanElzakker, 2021 ), abnormal immunological response and autoimmunity ( Leng et al, 2023 ), viral persistence ( Sherif et al, 2023 ), reactivation of latent Epstein-Barr virus ( Su et al, 2022 ), microvascular dysfunction ( Navis, 2023 ) , as well as coagulopathies and endotheliopathy ( Leng et al, 2023 ) have been suggested in the etiopathogenesis of PCS.…”
Section: Resultsmentioning
confidence: 99%
“…Hypotheses on pathogenic mechanisms implicate both systemic effects and sequelae from acute SARS-CoV-2 organ injury. Hyperinflammation (Proal and VanElzakker, 2021), abnormal immunological response and autoimmunity (Leng et al, 2023), viral persistence (Sherif et al, 2023), reactivation of latent Epstein-Barr virus (Su et al, 2022), microvascular dysfunction (Navis, 2023), as well as coagulopathies and endotheliopathy (Leng et al, 2023) Several other mechanisms are currently being researched, e.g., microbial dysbiosis (Gang et al, 2022), adverse effects of the viral spike protein on the angiotensin-converting enzyme two receptor, or inhibition of the gamma-aminobutyric acid (GABA) receptors (Manganotti et al, 2023).…”
Section: Pathogenesis Of Cognitive Impairment Associated With Pcsmentioning
confidence: 99%
“…Another prominent feature of LC is the array of neurological complications the sizeable chronic burden of which has been indicated by numerous studies ( 246 249 ). On a gross scale, a UK BioBank study analyzed brain MRI scans pre- and post-infection and observed a greater clinical burden of cognitive decline and radiological changes of reduction in brain size and gray matter atrophy affecting the hippocampus and orbitofrontal cortex in the post-infection group ( 250 ).…”
Section: Neutrophil Extracellular Traps In Long Covidmentioning
confidence: 99%
“…The microglia, macrophage cells located in the central nervous system (CNS), play a pivotal role in various neurological processes, such as neurogenesis, myelination, synaptic pruning, and inflammation. The activated microglia migrate to the site of injury or pathogen invasion to respond and start secreting pro/anti-inflammatory cytokines and neurotoxic molecules, such as interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, and nitric oxide (NO), respectively, leading to neuronal dysfunction. The activation also enables microglia to engulf foreign pathogens through phagocytosis, where phagosomes containing the pathogens fuse with acidic lysosomes to remove damaged neurons, debris, and apoptotic cells. During activation, microglia upregulate inducible nitric oxide synthase (iNOS), releasing excess nitric oxide (NO) that influences autophagy through interactions with the lysosomal machinery. Prolonged activation of microglia can lead to neuronal loss and contribute to neuroinflammatory and neurodegenerative diseases. , While rodent models have been used to study microglial cell activation and functions, research on human microglia has been limited due to the lack of availability of human microglial clone 3 (HMC3) cells . Recent reports have shown that patients suffering from long-COVID syndrome (LCS) and post-COVID-19 syndrome (PCS) exhibit neurological alterations, indicating SARS-CoV-2 impact on cellular dysfunction, and lysosomal egress pathways. Notably, oxidative stress appears to be a major driver of the pathophysiological mechanisms underlying LCS leading to the propagation of neuro-inflammation. In severe COVID-19 infections, patients are more likely to experience microgliosis, immune cell accumulation, and a higher risk of mortality. , Recent studies have revealed that single-stranded RNA fragments from the SARS-CoV-2 genome can activate innate immune receptors, triggering the secretion of pro-inflammatory cytokines. , However, understanding the dynamics of nitric oxide (NO) in neuroinflammation related to COVID-19 in the human brain is necessary to further explore.…”
Section: Introductionmentioning
confidence: 99%